Multiculturalism in Europe: Rise of Islam - Anton Minardi (Jayapangus Press, 2020)
After 9/11 there was a rise of “islamophobe” with the spreading of negative views on it besides anti-semite and anti-immigrants. Islam in some cases is seen as fundamentalism, radicalism and has a close meaning to terrorism. More than few were found some mistreatment to Muslim community in Europe such as shouting, blaming, exile and another form of discrimination in public sphere. This paper analysis European multiculturalism descriptifly. Europe is a region which not only recognises cultural and ethnic plurality but also multiculturalism. Its recognition was based on Europe’s identity as a modern and secular society. The population accepted other culture and ethnic rather than only welcomed immigrants. The migrants in Europe especially who came from Asia, Africa and Arab have differentiation in races, languages, habits, religions and their own views. In one hand, the differentiation enriches Europe culture but in the other hand, they have realised that it can be a threat to their identity. We found a lot of Europeans put their focus in particular on Islam which was spreading and growing as immigrants and new convertions. Nowadays they see the plurality especially to Islam as the integral religion both in private and public sphere as the challenge for their multiculturalism and reviewing to come, to assimilate, and to protect the European majority of Christians identity. Some European leaders agree that minority have to assimilate to the majority.